A language model-based approach for candidates with PhD profiling in a recruiting setting. (22nd March 2021) - Marrara, Stefania; Azzini, Antonia; Cortesi, Nicola
In the last decade, students facing a PhD course in Europe find terrible difficulties in reaching a permanent position in the academy. The situation gets worse when graduated PhDs have to migrate to public/private organisations that are not always ready to understand and improve the research experience. In such a situation, one of the most critical aspects is encountered immediately in the recruitment phase, since the keywords used in job offers portals are based on the employers' vocabulary and usually do not match the words that a researcher would use to describe her/his experience. Therefore, it is widely recognised that there is a need to define a system that can support a recruiters team in recruiting PhDs. The approach presented in this paper aims at designing a decision support tool able to guide the choices of recruiter of any company in the evaluation of profiles of candidates with PhD.